2005
DOI: 10.1111/j.1365-2567.2004.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Fas and Fas ligand in tuberculous lymphadenitis

Abstract: Summary The Fas/Fas‐ligand (FasL) system plays an important role in regulation of apoptosis and the immune response, and is exploited by mycobacteria to evade the immune response. This study was performed to investigate the distribution and levels of FasL and Fas in lymph node granulomas and sera of tuberculous lymphadenitis patients by immunohistochemistry and enzyme‐linked immunosorbent assay. The validity of soluble Fas (sFas) or soluble FasL (sFasL) as a diagnostic tool was also examined. Levels of sFasL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
(70 reference statements)
5
11
0
Order By: Relevance
“…The prominent elevation of TNF-a and Fas/FasL expression suggests the mechanisms through which this cascade is activated and is consistent with multiple studies from human TB [38,44,[51][52][53]. These data are also consistent with the starting hypothesis that apoptosis is one of the methods used by the host for eliminating infected cells without releasing viable bacteria -and suggest that the TNF-a pathway plays an important role in this.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The prominent elevation of TNF-a and Fas/FasL expression suggests the mechanisms through which this cascade is activated and is consistent with multiple studies from human TB [38,44,[51][52][53]. These data are also consistent with the starting hypothesis that apoptosis is one of the methods used by the host for eliminating infected cells without releasing viable bacteria -and suggest that the TNF-a pathway plays an important role in this.…”
Section: Discussionsupporting
confidence: 79%
“…However, FasL mRNA was higher in both CD14 1 and CD14 À cells from TB patients, suggesting a broad upregulation of this molecule in this cohort. This observation is consistent with earlier reports from human and murine M. tuberculosis infections [38,40,[42][43][44]. …”
supporting
confidence: 83%
“…1 The apoptosis of T cell induced by Fas/FasL binding serves to downregulate the immune response. The serum FasL levels are reported to be increased in patients with various clinical conditions such as viral infections, 2,3 malaria, 4 tuberculosis, 5 and autoimmune disorders. 6 There are also reports of deranged immune activation including raised FasL levels in certain geographic areas in apparently healthy persons.…”
mentioning
confidence: 99%
“…6 There are also reports of deranged immune activation including raised FasL levels in certain geographic areas in apparently healthy persons. 5,7 During one study involving blood levels of various cytokines in neurosurgical patients, an elevated serum FasL level in some control samples (apparently healthy blood donors) was observed that was found out to be reactive for human immunodeficiency virus enzyme-linked immunosorbent assay (HIV-ELISA). This prompted us to further investigate the serum FasL levels in HIV-ELISAreactive and nonreactive blood donors.…”
mentioning
confidence: 99%
See 1 more Smart Citation